Преобразуйте выражение б) sin(p+a)cos(2p-a)/cos(a-p)tg(p-a)

0 голосов
19 просмотров

Преобразуйте выражение б) sin(p+a)cos(2p-a)/cos(a-p)tg(p-a)


Алгебра (61 баллов) | 19 просмотров
Дан 1 ответ
0 голосов
Правильный ответ

Решите задачу:

\frac{sin(\pi +a)\cdot cos(2\pi -a)}{cos(a-\pi )\cdot tg(\pi -a)}=\frac{-sina\cdot cos(-a)}{cos(\pi -a)\cdot (-tga)}=\frac{-sina\cdot cosa}{-cosa\cdot (-tga)}=\frac{-sina\cdot cosa}{cosa\cdot \frac{sina}{cosa}}=\\\\=\frac{-sina\cdot cosa}{sina}=-cosa

(835k баллов)